1991
DOI: 10.1002/micr.1920120312
|View full text |Cite
|
Sign up to set email alerts
|

Major limb replantation in children

Abstract: This retrospective study evaluated patients under 18 years of age who underwent major limb replantation between 1976 and 1989 at Louisville Hand Surgery. The age of the 15 patients followed for between 1 and 8.5 years (mean 4.2 years) ranged from 2 to 17 years (mean 9.8). Of amputations, 40% were guillotine, 40% were limited crush-avulsions, 7% were extended crushing, and eight were of an upper extremity and seven of a lower extremity. Average warm/total ischemia times were 4.8/14.8 hr in failures and 1.1/7.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 45 publications
0
28
0
1
Order By: Relevance
“…[2][3][4][5][6][7] The overall success rate in our study was 89.8% (167/186). The patients who did not fulfil our inclusion criteria were treated promptly with an appropriate procedure except for those with strong contraindications to major limb reimplantation, such as multiple injuries, a prolonged warm ischaemic time greater than 12 hours and multilevel amputation with severe crush injuries.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[2][3][4][5][6][7] The overall success rate in our study was 89.8% (167/186). The patients who did not fulfil our inclusion criteria were treated promptly with an appropriate procedure except for those with strong contraindications to major limb reimplantation, such as multiple injuries, a prolonged warm ischaemic time greater than 12 hours and multilevel amputation with severe crush injuries.…”
Section: Discussionmentioning
confidence: 90%
“…Most articles simply describe the authors' experience. [2][3][4][5][6] Some have tried to use an algorithm for the treatment of traumatic amputation, 7 but the measurements and assessment have been subjective and the numbers of patients small. We have tried to improve the quality of prediction and decision-making for major reimplantation of the upper limb.…”
mentioning
confidence: 99%
“…[29][30][31] Therefore the missing limb can adversely affect the child's psychosocial development, replantation must be attempted in all amputation injuries of the children. Replantation was attempted in all cases admitted with total amputations.…”
Section: 2223mentioning
confidence: 99%
“…12 Another series with 3 distal forearm or wrist-level replants reported that 2 patients required revision amputations. 13 One report of a successful pediatric distal forearm level replant contains little information regarding surgical technique and few details of the functional results. 14 Of the papers discussing specifically hand replantations in the pediatric population, we were unable to identify any that discussed the particular challenge and outcomes of an amputation between the cartilaginous anlages of the growing carpus.…”
mentioning
confidence: 99%